2019
DOI: 10.1007/s11244-019-01170-5
|View full text |Cite
|
Sign up to set email alerts
|

Site Selective Detection of Methane Dissociation on Stepped Pt Surfaces

Abstract: We report a combined experimental and theoretical study comparing methane dissociation on three different platinum surfaces Pt(111), Pt(211), and Pt( 110)-(1 × 2). Reflection absorption infrared spectroscopy (RAIRS) was used to detect chemisorbed methyl species formed by dissociative chemisorption of CH 4 on specific surface sites and to measure surfacesite-specific sticking coefficients of CH 4 on the terrace, step, and ridge sites as function of incident translational energy. Methane dissociation is observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 81 publications
7
35
0
Order By: Relevance
“…CH 3 binds less strongly to the top site of Ni( 111) with E ad of −1.57 eV and becomes metastable on the fcc site of Pt(111) with an approximate E ad of ∼−1.33 eV (we can only find this geometry with a loose convergence criterion). The calculated adsorption energies and harmonic frequencies agree well with previous theoretical predictions, 14,16,18,26 although the predicted frequencies are systematically higher than the experimental ones, 14,22,33 due presumably to the intrinsic error in DFT as well as the harmonic approximation used in the theoretical calculations. Note that Gutieŕrez-Gonzaĺez et al 14 have applied vdW-corrected functionals to study CH 3 adsorbed on Pt surfaces and found similar site preference and site-specific vibrational frequencies as using PBE.…”
supporting
confidence: 83%
“…CH 3 binds less strongly to the top site of Ni( 111) with E ad of −1.57 eV and becomes metastable on the fcc site of Pt(111) with an approximate E ad of ∼−1.33 eV (we can only find this geometry with a loose convergence criterion). The calculated adsorption energies and harmonic frequencies agree well with previous theoretical predictions, 14,16,18,26 although the predicted frequencies are systematically higher than the experimental ones, 14,22,33 due presumably to the intrinsic error in DFT as well as the harmonic approximation used in the theoretical calculations. Note that Gutieŕrez-Gonzaĺez et al 14 have applied vdW-corrected functionals to study CH 3 adsorbed on Pt surfaces and found similar site preference and site-specific vibrational frequencies as using PBE.…”
supporting
confidence: 83%
“…The values in brackets correspond to those calculated using the PBE functional in a previous study by Jackson and co-workers. 33 Transition 1), where dissociation is seen to occur only on the ridge atoms of the surface using site selective detection by reflection absorption infrared spectroscopy 69 and with a previous study by Bisson et al 42 Figure 7(b) presents the same analysis as Fig. 7(a), but for the trapped trajectories, which shows that as the incident energy increases the fraction of trapped molecules that first hit the ridge atom tends to increase, although the analysis becomes less reliable at higher incident energies due to the lower number of trapped trajectories.…”
Section: Articlementioning
confidence: 99%
“…38 Finally, the reaction of methane is site-specific. 2,13,15,39 For all of these reasons, we will present in this work a detailed analysis of the results from the BOMD calculations and compare them to the results obtained on Pt(111) and Ni(111).…”
Section: Introductionmentioning
confidence: 99%